1998
DOI: 10.1111/j.2042-3306.1998.tb04514.x
|View full text |Cite
|
Sign up to set email alerts
|

Total and respirable airborne dust endotoxin concentrations in three equine management systems

Abstract: The concentrations of total and respirable airborne endotoxin in the breathing zone of a pony in 3 different management systems, on 8 occasions, are reported. Airborne endotoxin concentrations in all 3 systems were lower than those reported for many other agricultural environments. However, total airborne endotoxin concentrations in many of the conventional stables exceeded those which can induce puImonary inflammation and bronchial hyper-responsiveness in normal human subjects, and exceeded those which can in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 24 publications
8
107
1
3
Order By: Relevance
“…These observations confirm that attenuation of airway inflammation is due specifically to endotoxin. In conventional horse stables, airborne endotoxin concentrations exceed those on pasture (28) and those that can induce airway inflammation in human subjects (46,47). In our own stables, we observed that the endotoxin concentrations in the breathing zone of stabled horses are at least 10-fold higher than concentrations on pasture (unpublished data).…”
mentioning
confidence: 70%
“…These observations confirm that attenuation of airway inflammation is due specifically to endotoxin. In conventional horse stables, airborne endotoxin concentrations exceed those on pasture (28) and those that can induce airway inflammation in human subjects (46,47). In our own stables, we observed that the endotoxin concentrations in the breathing zone of stabled horses are at least 10-fold higher than concentrations on pasture (unpublished data).…”
mentioning
confidence: 70%
“…Furthermore, exposure to organic dust may cause rhinitis, asthma, bronchitis, or intrinsic lung disorders such as farmer's lung/allergic alveolitis. There are several studies now showing that working in a stable can have adverse health effects on the respiratory function similar to those experienced by farmers (Kristiansen & Lahoz, 1991;Mackiewicz et al, 1996;McGorum et al, 1998;Tutluoglu et al, 2002;Elfman et al, 2009). A majority of the personnel in the race horse stable had higher levels of lysozyme and MPO in nasal lavage than white collar workers.…”
Section: Discussionmentioning
confidence: 99%
“…The moldy hay environment in the present experiment contained slightly lower levels of airborne dust and airborne endotoxin compared with what has been reported for conventional stables (0.94 vs. 2.74 mg/m 3 , 18.2 vs. 19.76 ng/m 3 , respectively) but had a higher endotoxin concentration in the dust (19.4 vs. 7.57 ng/mg) (28). The alfalfa cubes environment in our study contained less endotoxin in dust than was reported for a pasture environment (2.8 vs. 4.85 ng/mg) (28), which is considered, to date, the ideal environment to achieve remission from heaves.…”
Section: Discussionmentioning
confidence: 40%